2014
DOI: 10.1016/j.micromeso.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of colloidal silicalite-1 at high temperatures

Abstract: Stable colloidal suspensions of silicalite-1 were prepared by hydrothermal treatment of clear precursor suspensions at high temperatures, 150 °C and 170 °C. The precursor suspensions were pretreated prior to hydrothermal treatment. Different pretreatment procedures were applied, namely ultrasonic treatment or heating at 45-60 °C, for different periods of time. In all cases, the size of the crystals decreased with increasing the time of pretreatment. The pretreatment procedure was found to influence the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Characterization on the Basic Physicochemical Properties of S-1zeolite. Figure 2A shows that the parent S-1 zeolite hydrothermally synthesized in this study according to the reported method 12 was well-crystallized. It had all the five characteristic peaks of the MFI topology (2θ = 7.9, 8.8, 23.1, 23.8, and 24.3°), and there was no diffraction peak related to impurity.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Characterization on the Basic Physicochemical Properties of S-1zeolite. Figure 2A shows that the parent S-1 zeolite hydrothermally synthesized in this study according to the reported method 12 was well-crystallized. It had all the five characteristic peaks of the MFI topology (2θ = 7.9, 8.8, 23.1, 23.8, and 24.3°), and there was no diffraction peak related to impurity.…”
Section: Resultsmentioning
confidence: 82%
“…Parent silicalite-1 (S-1) zeolite was synthesized followed a reported hydrothermal method. 12 First, a 220 g (25 wt. %) tetra-propylammonium hydroxide (TPAOH) solution was added dropwise into 312 g tetraethyl orthosilicate (TEOS) while stirring vigorously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Submicron and micrometer Silicalite‐1 zeolites were synthesized according to the literature . Typically, tetrapropylammonium hydroxide (TPAOH, 25 wt% aqueous solution), tetraethyl orthosilicate (TEOS) and distilled deionized water were mixed with stirring at room temperature to form a clear gel with a molar composition of m TPAOH : 25SiO 2 : 480H 2 O (where m = 3, 6 and 9, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Silicalite-1 zeolite was synthesized as follows [51]. Tetrapropylammonium hydroxide (TPAOH, 25% aqueous solution), tetraethyl orthosilicate (TEOS), and distilled water were mixed to obtain a clear suspension (9TPAOH:25SiO 2 :480H 2 O, molar composition).…”
Section: Catalyst Preparationmentioning
confidence: 99%